Modern architecture : a critical history - Frampton, Kenneth, 1930- (London : Thames & Hudson, 2016)
This acclaimed survey of modern architecture and its origins has become a classic since it first appeared in 1980. For this fourth edition Kenneth Frampton has added a major new chapter that explores the effects of globalization on architecture in recent years, the rise annd rise of the celebrity architect, and the way in which practices worldwide have addressed such issues as sustainability and habitat. The bibliography has also been updated and expanded, making this volume more complete and indispensable than ever.
417 illustrations
Keywords: Architectuur ; 20ste eeuw